RF and thermal hybrid input for ultra-low power semi-active UHF RFID tags - Tengku Mohamad, Tengku Norliza; Sampe, Jahariah; Berhanuddin, Dilla Duryha (2018 IEEE 14th International Colloquium on Signal Processing & Its Applications (CSPA), 2018)
Over the decades, RFID technology has attracted a lot of attention in industry, biomedical and military applications. Among the existing RFID tags, the robustness and high capability of semi-active UHF RFID tag makes it suitable for use in supply chain management, asset visibility and sensor networks. However, the major disadvantages of this tag are its limited lifetime issues and the need for periodic battery replacement. In this paper, a hybrid input of RF and thermal energy harvesting system is presented. The purpose is to combine an output DC voltage produced from both energy sources to solve the limited lifetime issues of the semi-active UHF RFID tags due to the need for batteries to power their specific applications. The proposed system is designed based on a standard 0.13 μm CMOS technology and simulated using pspice software. The simulated system can operate from the input voltages as low as 31.62 mV and is capable to harvest energy from individual harvester or both harvesters simultaneously. From the simulated results obtained, a maximum output voltage of 3.44 V can be harvested from 0 dBm single-input RF energy harvester. While a maximum output voltage of 3.40 V can be harvested when both RF and thermoelectric energy harvesters are harvested simultaneously at 0 dBm and 10 K temperature difference, respectively. The simulation is done with 1 ΜΩ resistive load and without the boosting circuit.